Cross-Border Trade Analysis Ecuador-Peru and its Commercial Development. Period 2017-2022 - Valencia-Valarezo, Pamela de las Mercedes (2024)
Cross-border regions are a place where various actors must work together to maintain social well-being. It is important to study and analyze their integration, as a strategy to prevent and resolve both internal and external problems. The objective of this article is to analyze the evolution of cross-border trade between Ecuador and Peru in the period 2017-2022. This work uses exploratory research and draws on academic articles, books, reports, manuals, electronic media and official websites. The orientation is qualitative and through the use of historical-logical and analytical-synthetic methods. The study shows the commercial exchange between Peru and Ecuador and reveals why it has been negative for the Ecuadorian economy. The analysis data shows that from Ecuador there is a greater import of products from Peru compared to the exports made to the neighboring country. The above has led to a negative balance in trade between the two countries. Both have made progress in the implementation of their national competitiveness plans and have designed examples of coordination, harmonization and cooperation, but there is still a lack of clear objectives and a general agreement on how to use and develop policies.